PENGARUH SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN INSTANSI PEMERINTAH PERWAKILAN BKKBN PROVINSI KEPULAUAN RIAU - Denny Saputra; Eni Duwita Sigalingging (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
The purpose of this research is to find out how the financial reports of the government agency of the BKKBN Representative of the Riau Islands Province are affected by the internal control system. To collect data, use a questionnaire. A total of 38 BKKBN representatives from Riau Islands Province were included in the sample of this study. The simple random sampling method was used in this study. Regression analysis, f tests, and t tests are performed on data using the SPSS for Windows program. The results of the research show that, in part, there is a significant influence between the control environment, risk assessment, control activities, information and communication, and monitoring on the quality of financial statements; at the same time, there are significant influences between the controlling environment, the assessment of risk, the control activity, the information and communications, and the monitoring of financial reporting quality.